The impact of enterprise systems in management decision making - C, Muthuvelayutham; T, Sugantha lakshm (Journal of Management and Science, 2012)
An Enterprise Resource Planning (ERP) system is composed of a basic transactional system and a management control system. Sammon et al. (2003) describes these 2 components of ERP systems as the solution to “operational” integration problems and “informational” requirements of managers. Thus, the extreme standardisation of business process inherent in ERP systems creates huge volumes of data without providing a clue for how to exploit it and may therefore not beneficial from a decision-making point of view. In this paper, decision-making theory and models are reviewed, focusing on how an ERP implementation might impact on these constructs. This paper is an analysis about centralisation of decision making in an organisation and its impact on performance at a local level.